Tradisi Sangkep Deha Truna Desa Adat Pilan Kabupaten Gianyar (Perspektif Pendidikan Agama Hindu) - Chika Aristia Santi, Ni Putu (Jayapangus Press, 2022)
The tradition of sangkep dehe truna which takes place at Pilan Traditional Village is a tradition that is carried out predominantly by the seka deha truna, namely children who have reached adulthood. The trend of globalization that dominates the realm of life reproduces the behavior and social structure of Hindus (especially young people) in the Pilan Traditional Village. This is marked by the lack of understanding of the younger generation of Hindus towards the tradition of sangkep dehe truna which has been going on from the past until now. While the research method used in this study is a qualitative method, with the determination of the research location at Pilan Traditional Village. Data sources consist of primary data and secondary data, the determination of informants is used based on a proportional sampling system. Data collection techniques through non-participant observation; unstructured interviews; literature study; and documentation. After that, data analysis was carried out using a triangulation pattern. Based on the results and discussion in this study, it was revealed that, (1) the process of implementing ngiasin three sana tradition includes: (a) the role of the seka deha truna before the tradition begins, (b) the role of the culmination of the ceremony, and (c) the role at the end of the ceremony; (2) the value of Hindu religious education applied in the niasin three sana tradition includes: (a) tri hita karana education with an explanation of parhyangan (tattwa values) explaining the value of belief, ritual value, sincerity value, and self-control value. Next, pawongan explains the value of gotong royong, ethical values ​​and the value of hard work. Furthermore, palemahan explains the value of sacrifice, the value of pleasure and the value of cultural preservation; and (3) the educational implications of sangkep dehe truna tradition include: strengthening the beliefs of the younger generation, shaping the ethics and morals of the younger generation, and strengthening the preservation of local wisdom.